Interannual Variability of the Daytime Equatorial Ionospheric Electric Field. Issue 5 (19th May 2018) - Yamazaki, Yosuke; Stolle, Claudia; Matzka, Jürgen; Liu, Huixin; Tao, Chihiro
Abstract: Understanding the variability of the ionosphere is important for the prediction of space weather and climate. Recent studies have shown that forcing from the lower atmosphere plays a significant role for the short‐term (day‐to‐day) variability of the low‐latitude ionosphere. The present study aims to assess the importance of atmospheric forcing for the variability of the daytime equatorial ionospheric electric field on the interannual (year‐to‐year) time scale. Magnetic field measurements from Huancayo (12.05°S, 75.33°W) are used to augment the equatorial vertical plasma drift velocity ( V Z ) measurements from the Jicamarca Unattended Long‐term Investigations of the Ionosphere and Atmosphere radar during 2001–2016. V Z can be regarded as a measure of the zonal electric field. After removing the seasonal variation of ∼10 m/s, midday values of V Z show an interannual variation of ∼2 m/s with an oscillation period of 2–3 years. No evidence of solar cycle influence is found. The Ground‐to‐topside Atmosphere‐Ionosphere model for Aeronomy, which takes into account realistic atmospheric variability below 30 km, reproduces the pattern of the observed interannual variation without having to include variable forcing from the magnetosphere. The results indicate that lower atmospheric forcing plays a dominant role for the observed interannual variability of V Z at 1200 local time. Key Points: Interannual variation of the equatorial electric field is examined GAIA model reproduces observations without variable magnetospheric forcing Lower‐atmospheric forcing dominates the variability at 1200 LT